Risk Factors Analysis in Patients Diagnosed with acute Lower Extremity DVT - حسن عامر; علي كفا; غانم أحمد (Latakia University Journal -Medical Sciences Series, 2023)
- Aim: To study risk factors in acute deep venous thrombosis of lower extremities patients and determine cases of primary unprovoked deep venous thrombosis, in which no predisposing factors were found. - Methods: A descriptive cross-sectional study was conducted, including patients diagnosed with acute DVT in lower extremities who were admitted to the vascular surgery division between 1-1-2022 and 31-12-2022. A detailed history was taken for all patients with a complete clinical examination, Duplex examination of lower extremities veins, in addition to laboratory evaluation and radiographic investigations when necessary. The diagnosis of Acute Deep Venous Thrombosis was made based on history, clinical examination and Duplex founding. Accordingly all collected data were analyzed. - Results: A total of 46 patients (56.5% males, 43.5 females, average age 56.7 ± 14.9 years) were enrolled in the study. The patients were distributed among all studied groups and the highest rate was by 51-70ys group. According to the anatomical distribution: 52.2% have DVT in the left extremity, 39.1% in the right and 8.7% in both extremities. There was found a predisposing factor in 54.3% of cases. The most common risk factors were: Malignancy 15.2% (Bladder tumors had highest rate followed by GI tumors), recent surgical procedure 15% (Abdominal interventions had the highest rate followed by gynecological procedures), smoking 37%, obesity and history of VTE 6.5%, history of immobilization and varicosis 4.3%. There was found no familial history in our study. - Conclusion: 54.3% of the patients had a predisposing factor for thrombosis. The most common were: Malignancy, surgical interventions, obesity and smoking.